(untitled) (Global Journal of Human-Social Science, 2015)
A sample of 1062 teachers was selected from an estimated population of 21,240 teachers spread across the 203 public secondary schools in Cross River State of Nigeria. An instrument called Teachers’ Affective Characteristics Questionnaire was used for data collection. The data were analysed using One-Way Analysis of Variance (ANOVA) test statistic. Results of the study showed that teachers’ academic disciplines significantly influence their job performances in terms of lesson delivery, students’ assessment/evaluation, classroom management, and student discipline. It was concluded that it was those teachers who had education as their disciplines that were better in overall job performance than their counterparts who do not belong to the discipline of education. The study concludes that teachers should be encouraged to pick higher degrees in education after their first degrees as this will improve their job performance.